Penggunaan Model Connecting, Organizing, Reflecting, Extending (Core) Untuk Meningkatkan Pemahaman Konsep Peraturan Perundangan Tingkat Pusat dan Daerah - Roy Ardiansyah, Hasan Mahfud, Fadhil Purnama Adi, Idam Ragil Widianto Atmojo, (Universitas Sebelas Maret, 2020)
Abstract. The purpose of this research is to improve the understanding of the material understanding of the concept of legislation at the central and regional levels using the CORE model for grade V students at SDN Pabelan 3 for the 2019/2020 academic year. This research is a classroom action research which is carried out in three cycles consisting of planning, implementing the action, observing, and reflecting. The research subjects were teachers and students of class V SDN Pabelan 3 for the 2019/2020 academic year, totaling 20 students.Data collection techniques using interviews, observation and documentation. The data analysis technique uses an interactive analysis model which consists of four components, namely data collection, data reduction, data presentation, and conclusion drawing. The data validity used content validity. The results show that the application of the CORE model can improve the understanding of the concept of legislation at the central and regional levels in class V SDN Pabelan students for the 2019/2020 academic year. In the initial conditions before takingaction, the pre-action students' completeness was 25%. With an average value of 54.2. After using the CORE model in cycle I, student completeness increased to 65% with an average value of 70.35, then in cycle II it increased to 85% with an average value of 81.15. Based on this research, it can be concluded that the application of the core model can improve the understanding of the concept of legislation at the central and regional levels in class V SDN Pabelan students for the 2019/2020 academic year.